Tendency of Generation-Y in Malaysia to Purchase Online Technological Products - Manimekalai, Jambulingam; Sorooshian, Shahryar; Caroline Sumathi, Selvarajah (Medwell Journals, 2016)
The purpose of this study is to investigate the determinants that influence the behavioural intention of online purchases among generation Y. The rapid growth of broadband web internet technology changes our life style of consumers by offering a wide variety of products online. Main novelty of this study is in its studied type of products. The study used modified TAM (Technology Adoption Model). The study addresses the key issues of perceived usefulness, perceived risk and perceived ease of use of consumers to purchase online technological products in order to establish a consensus among Gen Y. The sample size comprises of 200 undergraduate students and questionnaire is developed on Google drive and distributed through online survey methods using Facebook and Twitter. The analyses are completed with Pearson correlation coefficients and multiple linear regressions. The findings revealed that perceived usefulness and perceived risk of the website are significantly related to behaviour intention of online purchases among generation Y. The findings showed that Gen Y are willing to purchase online, if the retailers provide security on e-Transactions. The result will give useful information and attract more retailers to establish online business